Transformation of Religious Institution in Turkey from the Ottoman Sheikh ul-Islam to the Modern Diyanet Institution - Rosli, Nurhidayu (Journal of Islamic Thought and Civilization, 2022)
This paper offers a critical analysis of the body of offices responsible for the regulation of the public religious affairs in Turkey with a historical perspective from the Ottoman Empire to the current Republican period. The paper has a specific goal to explore how the public bodies regulating the religious life have played their role for the purpose of ensuring political and social control in the country by reviewing the religious institution during the Ottoman era and comparing within the Republican period under three different ruling ages: the Republican People’s Party, the multi-party and the AK Party. A significant volume of research has been conducted on the various aspects of public religious offices; and have been reviewed for this purpose by using historical research design. The findings show that during the Ottoman Empire, the regulation of the spiritual life was marked by a strong influence of the Sheikh ul-Islam . However, this institution experienced a huge decline after the establishment of the Republic of Turkey when the new secular political system started to confiscate the powers of the Sheikh ul-Islam one by one to abolish it altogether eventually in 1924. Diyanet has been established in its place as a new religious institution to provide services for some spiritual practices with much-restricted powers and roles under the authority of a ministry. Diyanet came to this day without much change in its capabilities until the AK Party came into the government which intended to make it a more active and functional department as part of what is called its major political strategy of Islamization through democratization. It can be summed up that after almost two decades of its tenure, findings show that the AK Party has partially achieved its goal to introduce a major change in the character of Turkish secularism from the protection of people from religious authoritarianism to protection of religion from political authoritarianism compared with other previous political parties. Keywords: Diyanet in Turkey, Religion in the Ottomans, Islamization via democratization, AK party